2007
DOI: 10.4314/as.v5i1.1539
|View full text |Cite
|
Sign up to set email alerts
|

Studies on seed-borne pathogens of some nigerian melons

Abstract: Fungi associated with three cultivars of melon seeds were investigated. The mycoflora were found to be more on the unshelled than on the shelled seeds of all the three cultirars tested. A total of nine fungal genera were isolated and identified while two were unidentified. C. vulgaris was infected with all the nine genera including the two unidentified genera. Percentage incidence of infection was observed to be higher for the unshelled than with the shelled seeds for all the cultivars. The genus, Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…have been isolated from "egusi" (Chiejina 2006;Bankole et al 2006a), OTA and CIT have not been detected in "egusi". Although Adebajo et al (1994) reported that Aspergillus ochraceus isolated from melon seed produced OTA in vitro, our study presents evidence that OTA along with CIT can contaminate "egusi" and that they can co-occur with AFs.…”
Section: Occurrence Of Ochratoxin and Citrininmentioning
confidence: 83%
“…have been isolated from "egusi" (Chiejina 2006;Bankole et al 2006a), OTA and CIT have not been detected in "egusi". Although Adebajo et al (1994) reported that Aspergillus ochraceus isolated from melon seed produced OTA in vitro, our study presents evidence that OTA along with CIT can contaminate "egusi" and that they can co-occur with AFs.…”
Section: Occurrence Of Ochratoxin and Citrininmentioning
confidence: 83%
“…ve Aspergillus spp. (Al-Kassim et al, 2000), salatalık tohumlarının embriyo, kotiledon, testa kısmından Macrophomina phaseolina (Sultana et al, 2009), kavun tohumlarında , en baskın tür sırasıyla Aspergillus niger, Rhizopus stolonifer ve en az oranda Aspergillus flavus (Chiejina 2006) izole edilmiştir. Habib et al (2007), yerel tohum satılan işletmelerden toplanılan farklı patlıcan çeşitlerinden Alternaria alternata, Aspergillus flavus, Culvularia lunata, Fusarium oxysporum ve Fusarium solani tespit etmişlerdir.…”
Section: Bulgular Ve Tartişmaunclassified
“…Many groups of fungi are known to contaminate Egusi seeds during storage. They reduce seed storability, quality, export and marketability potentials; and above all deposit a large number of metabolites in the seeds; some of which are toxic to humans (Chiejina, 2006;Atehnkeng et al, 2008). Fungi species belonging to the genera Rhizopus, Penicillium amongst others have been reported as seed pathogens of Nigerian stored Egusi seed.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi species belonging to the genera Rhizopus, Penicillium amongst others have been reported as seed pathogens of Nigerian stored Egusi seed. Many storage fungi that have been variously implicated in the spoilage of fruits and vegetables have been isolated from Egusi seeds by various authors (Chiejina, 2006;Aboloma et al, 2009;. Fungal deterioration of seeds occurs in form of rot, sclerotization of seed, and seed discolourization (Shetty 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation